Dramatugi Penyiar Radio - Nora, Hastika Yanti (Jurnal The Messenger, 2009)
Dramaturgy is the work of Erving Goffman. He wrote  "Presentation of Self in Everyday Life" in '1959. Following the theatrical analogy, Goffman spoke of a front stage and back stage. The front stage is that part of the performance that generally functions in rather fixed and general ways to define the situation for those who observed the performance. The back stage is situation where facts suppressed in the front or various kinds of informal actions may appear. A back stage is usually adjacent to the front stage, but it also cut off from it. Everyone in this world have to run his role in their everyday life. It also a radio announcer. As an actor, they have to be a nice and friendy person when they perform to make air personality, that is  a good   impression, from their audience.  But before their perform in the front stage, there so much to do to prepare in the backstage. The front and back stage is radio announcer dramaturgy.